Distance Learning from the Teachers’ Perspective and Students' Learning Experience Based on Self Confidence - Fatimah Malini Lubis; Nofirman Nofirman; Sudadi Sudadi; Zuraida Zuraida; Ilham Arief (Journal on Education, 2023)
This study aims to describe learning mathematics from the teacher's point of view and the experience of learning mathematics based on self-confidence. The results of research related to distance mathematics learning with reference to 4 aspects (learning strategies, pedagogic models, learning technology, and assessment) found that the learning strategy carried out by the teacher is to make students active by conducting questions and answers during video conferences, giving rewards and punishments, and delivering material assisted by electronic media such as PowerPoint, YouTube, and learning videos. The pedagogic model used is still providing problem-solving questions that are also integrated with group learning and the use of other learning resources. The assessment is carried out by considering the activity and intelligence of students, assisted by the Google Forms application. In addition, it was also found that student self-confidence had an impact on most of the indicators of the experience of learning mathematics at a distance, and vice versa.